2020
DOI: 10.1038/s41598-020-70216-6
|View full text |Cite
|
Sign up to set email alerts
|

Compression and stretch sensitive submucosal neurons of the porcine and human colon

Abstract: The pig is commonly believed to be a relevant model for human gut functions-however, there are only a few comparative studies and none on neural control mechanisms. To address this lack we identified as one central aspect mechanosensitive enteric neurons (MEN) in porcine and human colon. We used neuroimaging techniques to record responses to tensile or compressive forces in submucous neurons. Compression and stretch caused Ca-transients and immediate spike discharge in 5-11% of porcine and 15-24% of human ente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…2011; Mazzuoli‐Weber & Schemann, 2015b; Filzmayer et al . 2020). Individual ganglia of the SMP were stained with 20 μ m di‐8‐ANEPPS (1‐(3‐sulfanatopropyl)‐4‐[beta[2‐(di‐n‐octylamino)‐6‐naphthyl]vinyl] pyridinium betaine) by local intraganglionic application through a microinjection glass pipette.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2011; Mazzuoli‐Weber & Schemann, 2015b; Filzmayer et al . 2020). Individual ganglia of the SMP were stained with 20 μ m di‐8‐ANEPPS (1‐(3‐sulfanatopropyl)‐4‐[beta[2‐(di‐n‐octylamino)‐6‐naphthyl]vinyl] pyridinium betaine) by local intraganglionic application through a microinjection glass pipette.…”
Section: Methodsmentioning
confidence: 99%
“…For the detection of action potentials from enteric neurons an ultrafast neuroimaging technique was used. This technique, allowing the recording of neuronal activity with a high spatial and temporal resolution, was previously described in detail (Michel et al 2011;Mazzuoli-Weber & Schemann, 2015b;Filzmayer et al 2020). Individual ganglia of the SMP were stained with 20 μM di-8-ANEPPS (1-(3-sulfanatopropyl)-4-[beta[2-(di-n-octylamino)-6naphthyl]vinyl] pyridinium betaine) by local intraganglionic application through a microinjection glass pipette.…”
Section: Neuroimagingmentioning
confidence: 99%
“…Based on the structure and the localizations of ChAT+/SOM+/SP+ endings in the mucosa, we suggest a sensory function. To some extent, the identification of mechanosensitive ChAT+/SP+ neurons (Filzmayer et al 2020 ) supports this assumption.…”
Section: Structure Of Human Submucosal Neuronsmentioning
confidence: 93%
“…Unlike extrinsic spinal cord and vagal mechanoreceptors, whether their stimulation is sufficient seems to depend upon the length of the strain, rather than intramural tension (Hibberd et al, 2012). Experimental studies have shown that intestinal neurons have significant mechanosensitive responses to compression, shear stress, stretching, and hypoosmotic solutions (Hibberd et al, 2012;Dong et al, 2015;Kugler et al, 2015;Kugler et al, 2018;Filzmayer et al, 2020).…”
Section: Mechanosensitivity Of Intrinsic Enteric Neuronsmentioning
confidence: 99%